2020
DOI: 10.1016/j.jhep.2020.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Genotype correlates with the natural history of severe bile salt export pump deficiency

Abstract: Genotype correlates with the natural history of severe bile salt export pump deficiency Highlights NAPPED is the largest global database of genotyped patients with BSEP deficiency. The genotype of patients with BSEP deficiency predicts survival with native liver. Genotype predicts long-term benefit of interruption of enterohepatic circulation. Serum bile acids can be a surrogate marker for long-term outcome. Treatment of patients with BSEP deficiency should be based on genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 45 publications
2
103
2
Order By: Relevance
“…Notes: Case numbers in boldface indicate subjects of previous reports. 7,[9][10][11][12][13][14][15] Variants in boldface are novel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notes: Case numbers in boldface indicate subjects of previous reports. 7,[9][10][11][12][13][14][15] Variants in boldface are novel.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The genotype of patients with severe ABCB11 deficiency is associated with clinical outcomes. 7 TNC refers specifically to a status limited to infancy. Whether a patient with TNC will later prove to have BRIC, or even PFIC, cannot at present be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…35 Furthermore, a significant association was identified between lower post-SBD serum bile acids and long-term native liver survival: patients whose serum bile acids were <102 μmol/L after SBD survived up to 15 years with their native liver intact vs patients whose serum bile acids were ≥102 μmol/L, for whom less than half had this outcome. 35 Similarly, in a systematic review and meta-analysis evaluating studies with pre-and post-PEBD liver biochemistry values, patients with PFIC with reduced serum bile acids post-PEBD were more likely to have favourable clinical responses (ie, improved pruritus, decreased need for liver transplant). 59 Thus, the reduction in bile acids and improvement in clinical outcomes observed with SBD provide a strong rationale that disrupting enterohepatic circulation holds promise for treating patients with cholestatic liver disease.…”
Section: Interrup Ti On Of the Enterohepati C Circul Ati On A S A Tmentioning
confidence: 98%
“…Data from the NAPPED consortium also indicated that patient genotype, at least in the case of ABCB11-deficient PFIC for which data are available, may influence long-term outcomes following SBD; these data hint at a possibility for personalized medicine approaches in the future. 35 Inhibition of IBAT represents a pharmacologic approach for achieving the same ends as SBD: that is, interruption of the enterohepatic circulation of bile acids. IBAT is an integral brush border membrane glycoprotein that co-transports sodium and bile acids and is a major regulator of the bile acid pool size in animals and humans.…”
Section: Interrup Ti On Of the Enterohepati C Circul Ati On A S A Tmentioning
confidence: 99%
“…This change corresponded with a reduction in mean serum bile acids (from 363 μmol/L to 48 μmol/L, respectively). 13 Overall, a greater proportion of patients with lower serum bile acids after surgery survived with their native liver intact for up to 15 years versus those who had elevated serum bile acids post-surgery. 13 In addition, a systematic review and meta-analysis evaluating studies with pre-PEBD and post-PEBD liver biochemistry values found that patients with PFIC with reduced serum bile acids post-PEBD were more likely to have favourable clinical responses such as improved pruritus and decreased need for liver transplant.…”
Section: Introductionmentioning
confidence: 95%